2010
DOI: 10.1523/jneurosci.3762-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

Vibrissa-Based Object Localization in Head-Fixed Mice

Abstract: Linking activity in specific cell types with perception, cognition, and action, requires quantitative behavioral experiments in genetic model systems such as the mouse. In head-fixed primates, the combination of precise stimulus control, monitoring of motor output, and physiological recordings over large numbers of trials are the foundation on which many conceptually rich and quantitative studies have been built. Choice-based, quantitative behavioral paradigms for head-fixed mice have not been described previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
400
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 281 publications
(416 citation statements)
references
References 44 publications
10
400
0
1
Order By: Relevance
“…We used an identical trial structure to the texturediscrimination task to control for non-sensory differences across tasks. Mice could reach similar performance levels 22 compared to texture S1 during texture discrimination. a, Retrograde labelling of S2P and M1P neurons in S1 by AAV6-Cre and CTB-Alexa647 injection, respectively.…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…We used an identical trial structure to the texturediscrimination task to control for non-sensory differences across tasks. Mice could reach similar performance levels 22 compared to texture S1 during texture discrimination. a, Retrograde labelling of S2P and M1P neurons in S1 by AAV6-Cre and CTB-Alexa647 injection, respectively.…”
mentioning
confidence: 89%
“…Indeed, fine-scale analysis of principal whisker kinematics showed that sandpaper and pole contacts showed distinct kinematic features. Changes in whisker curvature that relate to contact forces 22 as well as the frequency of high acceleration-velocity 'slip' events associated with texture coding 11,12 were greater during texture discrimination compared to object localization (P , 0.001, Kolmogorov-Smirnov test; Fig. 4a and Supplementary Fig.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…In situations where there are unilateral contacts or where bilateral contacts are not simultaneous, RCP also appears to induce asynchronies in the relative timing of whisker movements on the two sides of the snout. Interestingly, when trained to make a specific discrimination, animals may modify this aspect of control and allow the whiskers to bend more strongly [28]. Further, when the whiskers touch a non-attended surface they may also show more pronounced bending [16], suggesting that RCP is not simply the consequence of some low-level reflex, but is related in some way to the current goals and focus of the animal.…”
Section: Introductionmentioning
confidence: 99%
“…The head fixed preparation, known for its wellcontrolled psychophysical conditions (stimulus delivery and response monitoring) in nonhuman primate studies, has been adapted to rodents by numerous groups [14][15][16][17][18][19]. Twophoton imaging of lateral cortical regions in awake, head-fixed animals poses a problem, since tilting the animal to adjust the imaging plane to be tangential to the cortical surface should be avoided.…”
Section: Introductionmentioning
confidence: 99%